Mass Cytometry Discovers Two Discrete Subsets of CD39−Treg Which Discriminate MGUS From Multiple Myeloma - Marsh-Wakefield, Felix; Kruzins, Annabel; McGuire, Helen M.; Yang, Shihong; Bryant, Christian; Fazekas de St. Groth, Barbara; Nassif, Najah; Byrne, Scott N.; Gibson, John; Brown, Christina; Larsen, Stephen; McCulloch, Derek; et al. (Frontiers in Immunology, 2019)
Multiple Myeloma (MM) is preceded by the clinically stable condition monoclonal gammopathy of undetermined significance (MGUS), which is defined by the presence of a monoclonal protein and less than 10% malignant plasma cell infiltration in the bone marrow (BM). Critical immune events that discriminate MGUS from newly diagnosed MM (NDMM) patients remain unknown, but may involve changes in the regulatory T cell (Treg) compartment that favour myeloma growth. To address this possibility, we used mass cytometry to interrogate the distribution of multiple subsets within CD25+CD27low/negTreg in matched BM and peripheral blood (PB) of MGUS and NDMM patients. Both mass cytometry and flow cytometry confirmed a dominance of CD39-Treg within the Treg compartment in BM and PB of NDMM patients compared to an even distribution of CD39-Treg and CD39+Treg in MGUS patients. Unsupervised clustering displayed a phenotypic organisation of Treg into 25 metaclusters that confirmed Treg heterogeneity and identified two subsets which emerged exclusively within CD39-Treg of NDMM patients. One subset was found in both BM and PB that phenotypically resembled activated Treg based on CD45RO, CD49d, and CD62L expression; another subset resembled BM-resident Treg based on its tissue-resident phenotype characterised by CD69 expression, a lack of CD62L and CD49d expression and restricted location within the BM. PD-1 and TIGIT coexpressed on activated Treg, while PD-1 was expressed at higher levels on BM-resident Treg then on activated Treg. Both subsets produce Perforin and Granzyme B. In conclusion, the use of mass cytometry discovered two discrete subsets of CD39-Treg which may be permissive of myeloma growth. Understanding the regulatory properties of these subsets may also advance MGUS and MM diagnosis, prognosis, and therapeutic implications for MM patients.